State and people with disabilities: An analysis of the state's duty to promote access to assistive technologies for people with disabilities through extrafiscality (Research, Society and Development, 2023)
This article aims to analyze the duty of the State to implement extra-fiscal public policies aimed at people with disabilities in order to promote access to assistive technologies. To this end, it used the narrative bibliographic review methodology to analyze the concept of "person with disabilities", as well as the laws that benefit these people. Initially, the construction of the concept of person with disabilities was explored, presenting the most archaic term to the most accurate, which is currently used. After the conceptualization, the research entered the tax area working on the idea of taxes, as well as their functions, namely: taxation and extrafiscality, the latter being used as a guiding thread for the implementation of the public policy of access to assistive technologies. In addition, the promotion of the fundamental rights of people with disabilities through extra-tax policies was discussed. Finally, in the final considerations it was verified that the State must apply public policies of an extra-fiscal nature, because the access of people with disabilities to assistive technologies concretizes the principle of isonomy, making equality effective in the material field.